2011
DOI: 10.1155/2011/142739
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Activity of Dried‐ and Fermented‐Processed Virgin Coconut Oil

Abstract: The present study aims to determine the hepatoprotective effect of MARDI-produced virgin coconut oils, prepared by dried- or fermented-processed methods, using the paracetamol-induced liver damage in rats. Liver injury induced by 3 g/kg paracetamol increased the liver weight per 100 g bodyweight indicating liver damage. Histological observation also confirms liver damage indicated by the presence of inflammations and necrosis on the respective liver section. Interestingly, pretreatment of the rats with 10, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 56 publications
6
49
1
2
Order By: Relevance
“…However, a reduction in the liver weight of the AmSO0.5 and AmSO1.0 groups compared to CtrlAmSO group was observed ( Table 2). The hepatoprotective effect has been identified in coconut oil, the study of Zakaria et al, (2011). Treatment with virgin coconut oil reduced the hepatotoxicity induced by acetaminophen, reduced the dosages of liver enzymes and improved liver morphology.…”
Section: Discussionmentioning
confidence: 99%
“…However, a reduction in the liver weight of the AmSO0.5 and AmSO1.0 groups compared to CtrlAmSO group was observed ( Table 2). The hepatoprotective effect has been identified in coconut oil, the study of Zakaria et al, (2011). Treatment with virgin coconut oil reduced the hepatotoxicity induced by acetaminophen, reduced the dosages of liver enzymes and improved liver morphology.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in some experiments it has been shown that virgin coconut oil has hepato-protective activity on rabbits (Zakaria et al, 2011). Moreover, it was shown that the replacement of soyabean oil by coconut oil in the feed of broilers lowered the level of low density lipoprotein (LDL)-cholesterol and favourably affected lipid profile in serum (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A slightly modified method of Zakaria et al, (2011) for CCl 4 toxicity assay was used. The rats were randomly divided into six groups each consisting of six rats (n = 6).…”
Section: -Induced Toxicitymentioning
confidence: 99%